Frontispiece: Hybridization Gap and Dresselhaus Spin Splitting in EuIr4In2Ge4. Issue 32 (3rd August 2015) - Calta, Nicholas P.; Im, Jino; Rodriguez, Alexandra P.; Fang, Lei; Bugaris, Daniel E.; Chasapis, Thomas C.; Freeman, Arthur J.; Kanatzidis, Mercouri G.
<x xml:space="preserve">Abstract</x> Intermetallic Phases M. G. Kanatzidis and co‐workers describe in their Communication on page 9186 ff. an intermetallic semiconductor that adopts a non‐centrosymmetric structure. The band gap in EuIr4In2Ge4 is a direct result of strong IrIr bonding.